Study of PVA Based Nanocomposite Polymer Gels Containing Weak Aliphatic Dicarboxylic Acids. Issue 3 (7th January 2020) - Kumar, Rajiv; Kaur, Simranpreet; Singh, Navneet; Sharma, Honey; Sharma, Shuchi
Abstract : In this paper, nanocomposite polymer gel electrolytes have been prepared by using nano-size fumed silica (SiO2 ), polyvinyl alcohol (PVA), dimethyl sulfoxide (DMSO) and weak aliphatic acids (oxalic acid (OA), malonic acid (MA), succinic acid (SA) with different dissociation constant values) and characterized by ionic conductivity, pH and viscosity studies. The ionic conductivity of liquid electrolytes has been found to depend upon the dissociation constant values of the acids, which has been explained on the basis of inductive effect. The decrease in ionic conductivity of electrolytes observed with the addition of polymer has been explained due to increase in viscosity. The increase in conductivity of gel electrolytes with the addition of nano-filler has been explained by double percolation threshold model. Maximum room temperature conductivity of 2.12 x 10 −3 S/cm, 7.3 x 10 −4 S/cm, 5.8 x 10 −4 S/cm have been obtained for nanocomposite gel electrolytes containing DMSO + 1M OA, MA, SA+ 10 wt% PVA at 6 wt% SiO2 respectively.